2007
DOI: 10.1534/genetics.106.061457
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Maps of thedwarfand Normal Lake Whitefish (Coregonus clupeaformis) Species Complex and Their Hybrids Reveal the Genetic Architecture of Population Divergence

Abstract: Elucidating the genetic architecture of population divergence may reveal the evolution of reproductive barriers and the genomic regions implicated in the process. We assembled genetic linkage maps for the dwarf and Normal lake whitefish species complex and their hybrids. A total of 877 AFLP loci and 30 microsatellites were positioned. The homology of mapped loci between families supported the existence of 34 linkage groups (of 40n expected) exhibiting 83% colinearity among linked loci between these two familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 139 publications
(159 reference statements)
4
45
1
Order By: Relevance
“…As the species are young and can be crossed easily, incompatible loci seems more probable than large genomic rearrangements (Moyle and Graham 2005). Genetic incompatibilities between species detected on the basis of segregation distortion have been suggested in many cases, including lake whitefish (Rogers and Bernatchez 2007; Rogers et al 2007), Drosophila (Phadnis and Orr 2009), Nasonia (Gadau et al 1999; Niehuis et al 2008), and some plant species (Foolad et al 1995; Whitkus 1998; Fishman et al 2001; Myburg et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…As the species are young and can be crossed easily, incompatible loci seems more probable than large genomic rearrangements (Moyle and Graham 2005). Genetic incompatibilities between species detected on the basis of segregation distortion have been suggested in many cases, including lake whitefish (Rogers and Bernatchez 2007; Rogers et al 2007), Drosophila (Phadnis and Orr 2009), Nasonia (Gadau et al 1999; Niehuis et al 2008), and some plant species (Foolad et al 1995; Whitkus 1998; Fishman et al 2001; Myburg et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported high levels of segregation distortion, greater than 15% of loci at P  < 0.05, within hybrid maps across a variety of taxa, including interspecific crosses between Mimulus guttatus and M. nastutus [8], Lepomis cyanellus and L. megalotis [53], and Nasonia giraulti and N. vitripennis [54] and between intraspecific crosses of Salvelinus alpinus [55], M. guttatus [56], Ceratodon purpureus [57], Coregonus clupeaformis [58], and Tigriopus californicus [59]. Divergence time estimates between parental lineages used for several of these maps ranged from 0.1-0.2 MYA to 13–16 MYA [60-63].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of AFLP for genome scans has limitations. AFLP loci may be associated with a particular region of the genome, possibly missing section of the genome that are under natural selection [100]. In addition to the relatively few loci available for the genome scan, this concentration of restriction sites may account for the failure of AFLP to find outliers [101].…”
Section: Discussionmentioning
confidence: 99%